FRAGMENTED AGRARIAN SPACE: BUILDING BLOCKS AND MODERNISATION TRAJECTORIES. THE CASE OF SLOVENIA - Potočnik Slavič, Irma (Quaestiones Geographicae, 2017)
Production, processing and consumption within Slovenian agrarian space are fragmented due to physical constraints (72.4% of the territory categorised as ANC) and socio-geographic factors. Based on available data, five essential building blocks of contemporary Slovenian agrarian space (available land, change management, integrated circular economy, adjustable policies, and flexibility of institutions) are discussed. Interrelations among the building blocks shape the modernisation trajectories of approx. 70,000 agricultural holdings in Slovenia. The coexistence of three modernisation trajectories, i.e. practised autarky, various forms of pluri-activity, and small-scale intensive and innovative modernisation, creates a complex mosaic. The governance of multifunctional and multi-structured agrarian space is becoming more demanding.